2022
DOI: 10.1155/2022/7479299
|View full text |Cite
|
Sign up to set email alerts
|

Masking Ability of Bleach Shade Composite Resins in Different Thicknesses

Abstract: Introduction. In recent years, the use of bleach shade composite resins has increased due to the high esthetic demands. The aim of the present study was to investigate the masking ability and translucency of several bleach shade composite resins. Materials and Methods. In this in vitro study, 180 discs from 9 bleach shade composite resins of 5 brands (G-aenial Anterior, Gradia Direct, Charisma Diamond, Estelite Sigma Quick, and Renamel Microfill) in thicknesses of 0.5, 1, 1.5, and 2 mm were prepared. The color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…These additives besides increasing the darkness of the background, they might agglomerate and change the macroscopic surface features as the surface roughness that greatly affect the optical properties of resin composite. Additionally, the findings of increased darkness of resin composite when loaded with high concentration of GONPs also agree with Lee and others [ 51 ] who revealed that if the filler size is constant, the higher filler load might produce a rough resin composite surface with subsequently reflected light scattering in different angles that lowers the translucency with a more darkening effect [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These additives besides increasing the darkness of the background, they might agglomerate and change the macroscopic surface features as the surface roughness that greatly affect the optical properties of resin composite. Additionally, the findings of increased darkness of resin composite when loaded with high concentration of GONPs also agree with Lee and others [ 51 ] who revealed that if the filler size is constant, the higher filler load might produce a rough resin composite surface with subsequently reflected light scattering in different angles that lowers the translucency with a more darkening effect [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 85%
“…Additives incorporation to resin composite can change the refractive index of the matrix and increase the perceived light scattering making the material less translucent [ 51 , 52 , 58 ]. These additives besides increasing the darkness of the background, they might agglomerate and change the macroscopic surface features as the surface roughness that greatly affect the optical properties of resin composite.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, resin composites were not colored to any agents. Translucency is influenced by various factors; the thickness of composites, [10] pigments and other chemical ingredients of the material [11] and light-curing protocol [12]. This study used composite samples of A2 tons and equal thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Extra white shade resin composites have been lately introduced by many manufacturers to restore bleached teeth. The color stability of those extremely white teeth shade composite restorations is very important for the patients seeking those peculiar shades 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Bleach shade composites are luminous and more translucent than ordinary shades, they have lower translucency and higher masking ability. Lately there is an increased demand to use bleach shade composites, as patients request high aesthetic levels, and they are similar to tooth whitening treatment modalities 3 .…”
Section: Introductionmentioning
confidence: 99%